2014
DOI: 10.1590/jvb.2014.019
|View full text |Cite
|
Sign up to set email alerts
|

Vascular ultrasonography for follow-up of endovascular repair of abdominal aorta aneurysms

Abstract: Background: There is little information available on follow-up of abdominal aortic aneurysm patients treated with endovascular repair using vascular ultrasonography in Brazil or on how it compares with the results of angiotomography. Since ultrasonography is an examination that is risk-free, inexpensive and widely available, it is a very attractive method. In this study we attempted to evaluate the sensitivity and specificity of vascular ultrasonography for follow-up of these patients by comparing the method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…The study conducted by França et al ( 11 ) showed that ultrasound had a sensitivity and specificity of 54.5% and 92.8%, respectively, for the detection of endoleaks, when compared with CT angiography in a sample of 50 examinations, as well as showing a statistically significant correlation for the measurement of the aneurysm sac ( R = 0.97; p < 0.001). Moraes Filho et al ( 12 ) found that ultrasound had a sensitivity of 75% and a specificity of 96% for the detection of endoleaks and that there was a statistically significant correlation for the aneurysm sac diameter ( R = 0.91).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by França et al ( 11 ) showed that ultrasound had a sensitivity and specificity of 54.5% and 92.8%, respectively, for the detection of endoleaks, when compared with CT angiography in a sample of 50 examinations, as well as showing a statistically significant correlation for the measurement of the aneurysm sac ( R = 0.97; p < 0.001). Moraes Filho et al ( 12 ) found that ultrasound had a sensitivity of 75% and a specificity of 96% for the detection of endoleaks and that there was a statistically significant correlation for the aneurysm sac diameter ( R = 0.91).…”
Section: Discussionmentioning
confidence: 99%
“…It should be borne in mind that obesity and inadequate bowel preparation are limiting factors for abdominal ultrasound examination, due to an inappropriate acoustic window. Other limitations include examiner-dependence and physical variations of patients ( 12 , 13 ) . Nevertheless, ultrasound is a reproducible, less expensive, more widely available method than is CT angiography and does not involve the use of iodinated contrast or radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Os aneurismas de artérias viscerais (AAVs) e pseudoaneurismas de artérias viscerais (PAAVs) são raros, com incidência entre 0,01 e 0,2% 1 . Com o avanço de técnicas em exames de imagem como a angiotomografia computadorizada (angioTC) de abdômen e o ultrassom Doppler (USD) 2,3 para detecção de doenças intra-abdominais, juntamente com maior manipulação das vias biliares, a taxa de prevalência e o achado incidental dos aneurismas têm aumentado. Os AAVs são causados principalmente por hipertensão, aterosclerose, displasia e doenças do colágeno, enquanto os PAAVs estão associados a traumas, lesões iatrogênicas, inflamação ou infecções 4 .…”
Section: Introductionunclassified